Design and short‐circuit current breaking test verification of a 72.5 kV single‐break fast vacuum circuit breaker. Issue 11 (12th March 2022) - Guan, Chen; Yao, Xiaofei; Chen, Xinggui; Zhang, Luyang; Zhang, Ran; Liu, Zhiyuan; Wang, Jianhua; Geng, Yingsan; Ma, Hui
Abstract: Fast clearing of a short‐circuit fault is vital to increase the transmission capacity of power grid transmission lines and improve the transient stability of a power system. A fast vacuum circuit breaker (FVCB) is a good candidate to realize quick elimination of a short‐circuit fault. The original contribution of this paper is to present the design of a 72.5 kV single‐break FVCB and its verification of short‐circuit breaking performance. A specially designed 72.5 kV vacuum interrupter, with floating shields and reduced mass of moving components, was developed. An electromagnetic repulsion actuator was used to provide a high initial opening speed, V1, of 5 m/s over half of the full‐contact gap and a relatively low average opening speed, V2, of 1.59 m/s in the full contact gap of 30 mm. The high‐designed V1 and low‐designed V2 were achieved with the aid of a deliberately designed oil buffer. The opening and closing time of the designed 72.5 kV FVCB was 1.2 ± 0.04 ms and 18 ± 0.20 ms respectively. The terminal fault test duty of T100s(b), carried out on the 72.5 kV FVCB, demonstrated both the 40 kArms and 80 kArms short‐circuit current breaking performance. The short‐circuit current breaking arcing time windows of FVCB, including the minimum arcing time, the maximum arcing time, and the middle arcing time, was verified to fulfill the requirement of the international standard, IEC 62271‐100 2017, and the Chinese standard, GB/T 1984–2014, both for the 40 kArms and 80 kArms switching cases, respectively. Further development of the 72.5 kV single‐break FVCB would benefit the development of ultra‐ or extra‐high voltage FVCBs by reducing essential numbers of series‐connected breaking units.